Chromovitrectomy - Musat, Ovidiu (Rom J Ophthalmol, 2016)
The term “chromovitrectomy” has been coined to define the use of vital dyes in vitreoretinal surgery. The basic concept for the application of vital dyes during vitreoretinal surgery is to assist in highlighting preretinal membranes and tissues which are very thin and semitransparent and thus difficult to detect. Various dyes are currently being used in routine clinical procedures, however, the ideal staining agent has not yet been found. The vital dyes indocyanine green, infracyanine green, and brilliant blue stain the internal limiting membrane, trypan blue and triamcinolone acetonide help to visualize the epiretinal and vitreous membranes. New dyes with a better safety profile than the synthetic ones are important for optimizing the outcome of modern ophthalmic surgery and natural dyes, such as lutein, offer a potentially safer and more efficient method of identifying intraocular structures such as vitreous and ILM. Any dye, which is intravitreally injected has the potential to become toxic.